Scientific Validity of Efficacy of Homoeopathic Hair Care Management (Homoeopathy for All, 2024)
Homoeopathy is considered as one  of the very best alternative system  for treating hair loss. Hair loss can  affect scalp or entire body. It can  be the result of heredity, hormonal  changes, medical conditions or  medications. Anyone like men,  women and children can experience  hair loss. Baldness typically refers  to excessive hair loss from scalp.  Hereditary hair loss with age is the  most common cause of baldness.  Some people prefer to let their  baldness run its course untreated and  unhidden.
Keywords: Scientific; Homoeopathic